An Overview of Vaginoplasty Techniques: Spotlight on the Efficacy of the Horseshoe Labia Minora Flap - Begum, Rasheedha; Philip, Manimegala; Kandasamy, Mahadevan; Shanmugam, Sridevi; Muthachari, Sugumar (Indian Journal of Plastic Surgery, 2025)
Mayer–Rokitansky–Küster–Hauser (MRKH) syndrome involves vaginal agenesis and variable uterine development, often accompanied by renal, skeletal, and auditory anomalies. The primary objective of treatment is to reconstruct a neovagina that closely resembles the natural anatomy, enabling normal sexual function. This study evaluates various vaginoplasty techniques performed at our institution and their outcomes.This retrospective study, conducted from January 2012 to January 2024, includes patients who underwent different types of vaginoplasty, including the McIndoe, Singapore flap, islanded pudendal flap, labia minora flap, and horseshoe modification of the labia minora flap. Procedures were chosen based on clinical examination. Outcomes were assessed using an institutional scoring system evaluating vaginal length, introitus diameter, neovaginal skin quality, and pain during intercourse.Twenty patients of primary vaginal agenesis (aged 18–27) diagnosed clinically and confirmed with pelvic MRI underwent vaginoplasty by the same surgical team. One (14.28%) patient of the McIndoe procedure experienced graft contracture, which was released and regrafted, while another (14.28%) had partial graft loss managed conservatively. No significant complications occurred in the remaining patients. All used a postoperative vaginal mould for three months. The average follow-up period was 18 months, with neovaginal length ranging from 6 to 10 cm.The horseshoe modification of the labia minora flap offers a reliable, effective approach for vaginal reconstruction in cases of MRKH syndrome. This technique fulfils the basic tenets of plastic surgery, namely the restoration of form and function. The simplicity of the procedure and relatively short learning curve render it an attractive flap option even for the novice plastic surgeon.
Keywords: vaginoplasty; Mayer–Rokitansky–Küster–Hauser syndrome; McIndoe procedure; pudendal flap; Singapore flap; labia minora flap